Psychosocial impact of COVID‐19 on caregivers and adolescents and young adult survivors of childhood cancer. Issue 6 (23rd March 2023) - King‐Dowling, Sara; Hammer, Shannon N.; Faust, Haley; Madden, Rebecca; Drake, Sarah; Ahmed, Annisa; Albee, May; Deatrick, Janet A.; Daniel, Lauren; Pai, Ahna; Freyer, David; Psihogios, Alexandra M.; et al.
Abstract: Background: Caregivers and adolescents and young adult (AYA) cancer survivors may be at greater psychosocial risk from the COVID‐19 pandemic than healthy peers due to complex and traumatic medical histories. This study describes COVID‐19‐related event exposures, impact, and distress among a large sample of caregivers and AYA cancer survivors and the relationship of these variables to demographic and cancer characteristics. Procedure: From May 2020 to December 2021, 422 caregivers and 531 AYA survivors completed the COVID‐19 Exposures and Family Impact Survey (CEFIS) and CEFIS‐AYA, respectively. Total COVID‐19‐related exposures, average COVID‐19‐related impact, and COVID‐19‐related distress were calculated. Conventional content analysis was used to analyze free‐text responses about the negative and positive effects of COVID‐19. Results: Caregivers and AYA reported an average of 7.4–7.8 COVID‐19 exposures to pandemic‐related events and a slightly negative impact of COVID‐19 across psychosocial domains, with some positive impacts reported. COVID‐19‐related distress was moderate and clinically meaningful (4.9–5.2/10) for AYA and caregivers. Racial and ethnically minoritized AYA and caregivers reported higher COVID‐19‐related distress than non‐Hispanic white caregivers. For AYA, distress was also higher among female, college‐age (18–22 years), and long‐term survivors compared with males, younger AYA, White and those recently off treatment. CEFIS outcomes remained relatively stable over time. Conclusions: COVID‐19 had a significant and consistent negative impact on caregivers and AYA survivors. Racial and ethnically minoritized families and female, college‐age, and long‐term AYA survivors may require additional psychosocial support. Assessing for COVID‐19 impact and distress is important in pediatric oncology to evaluate adjustment and plan targeted interventions.